CONSTRUCTION MANAGEMENT PLANNING OF AL-JABBAR GREAT MOSQUE - Fairuz Nur Faadhilah, Nadhifah
West Java has one of the largest Muslim populations in Indonesia. Islam has a big influence on the people’s culture and daily activity. However, West Java does not have its own Great Mosque that can become a centre for religious activities. Therefore, the Government of West Java initiated the construction of Al-Jabbar Great Mosque, which located in Cimencrang, Gedebage District, Bandung. This final project will discuss about the construction management planning of Al-Jabbar Great Mosque. Management planning of Al-Jabbar Great Mosque consists of determining the construction methods, quantity take off, construction schedule, and calculating the project value. Construction methods management includes safety, health, and environment also quality control. Project value is calculated from direct cost and indirect cost along with the required tax. For scheduling, Microsoft Project is used to determine the duration and S curve of the project. This project takes 326 working days with a project value of Rp227.286.792.000,00.